2018
DOI: 10.3390/nu10101366
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Targeting of the AKT PH Domain Activates AKT/GSK3β/FOXO1 Signaling and Improves Glucose Metabolism

Abstract: Chlorogenic acid (CGA), a bioactive component in the human diet, is reported to exert beneficial effects on the regulation of glucose metabolism. This study was designed to investigate the specific target of CGA, and explore its underlying mechanisms. Beneficial effects of CGA in glucose metabolism were confirmed in insulin-treated human hepatocarcinoma HepG2 cells. Protein fishing, via CGA-modified functionalized magnetic microspheres, demonstrated the binding of CGA with protein kinase B (AKT). Immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…To enhance our understanding of the increased IR in Mas ‐/‐ mice, we examined the expression of glucose‐metabolism‐related proteins in the liver. GSK3β is considered to interact with FOXO1 to regulate gluconeogenesis 14 . In the present study, phospho‐FOXO1 and phospho‐GSK3β levels were decreased in Mas −/− mice and mirrored the markedly increased expression of G6Pase and PEPCK (Figure 1L), the critical rate‐limiting enzymes in the gluconeogenic pathway.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…To enhance our understanding of the increased IR in Mas ‐/‐ mice, we examined the expression of glucose‐metabolism‐related proteins in the liver. GSK3β is considered to interact with FOXO1 to regulate gluconeogenesis 14 . In the present study, phospho‐FOXO1 and phospho‐GSK3β levels were decreased in Mas −/− mice and mirrored the markedly increased expression of G6Pase and PEPCK (Figure 1L), the critical rate‐limiting enzymes in the gluconeogenic pathway.…”
Section: Resultssupporting
confidence: 58%
“…GSK3β is considered to interact with FOXO1 to regulate gluconeogenesis. 14 In the present study, phospho-FOXO1 and phospho-GSK3β levels were decreased in Mas −/− mice and mirrored the markedly increased expression of G6Pase and PEPCK ( Figure 1L), the critical rate-limiting enzymes in the gluconeogenic pathway. In terms of fatty acid metabolism, Mas −/− mice showed a significant increase in FAS, the key enzyme required for TG synthesis, and a slight increase in ACCα, but showed a notable decrease in ATGL, a rate-limiting enzyme in TG metabolism, and no change in phospho-HSL ( Figure 1M).…”
Section: Mas −/− Mice Exhibit Impaired Glucose Tolerance Ir and Gsupporting
confidence: 63%
“…The effects of CGAs have been related to an inhibition of carbohydrate digestion by inhibiting amylase [ 30 , 31 ], to the preventing action of glycosidase in the brush border of the small intestine [ 32 ], to modulation of gastrointestinal peptides shifting glucose absorption to more distal region in the GI tract [ 10 ] and also to a reduction of hepatic glucose output [ 33 ]. Recent investigations have suggested that CGA could regulate glucose metabolism by directly interacting with the AKT (protein kinase B) related pathway, leading to glycogen synthase activation and lowering blood glucose [ 34 ]. Based on this literature, we aimed to evaluate the impact of a nutritional intake of CQAs from maté extract on glycemic control in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were then extracted and quantified according to a previously reported method. [ 42 ] Protein lysates were treated with LA‐modified MMs (as shown in Figure S3, Supporting Information) and incubated overnight at 4 °C to capture the target protein. The MMs were magnetically separated and washed with PBS.…”
Section: Methodsmentioning
confidence: 99%